Current pharmacotherapy of cryptosporidiosis: an update of the state-of-the-art. (22nd November 2021) - Schneider, Anne; Wendt, Sebastian; Lübbert, Christoph; Trawinski, Henning
ABSTRACT: Introduction : Cryptosporidiosis has emerged as a major cause of diarrheal disease worldwide. It has especially serious health consequences for young, malnourished children living in endemic areas and for individuals with highly impaired T-cell function, such as HIV-positive individuals with low CD4 counts or immunosuppressed solid-organ transplant recipients. Areas covered : A selective literature search using PubMed was performed to review the available therapeutics to treat cryptosporidiosis, as well as related advances in drug development. Expert opinion : The only FDA-approved antiparasitic treatment in immunocompetent patients is nitazoxanide; however, it has failed to demonstrate convincing effectiveness among HIV-positive patients, immunosuppressed individuals and malnourished children. Thus, restoring HIV-positive patients' cellular immune response through effective antiretroviral therapy (ART), or reducing or changing immunosuppressive drugs, is important. Several new targets have been identified for chemotherapy, and the development of drugs for these targets has progressed, including parasite kinases, nucleic acid synthesis and processing, proteases and lipid metabolism. Candidate drugs that have been shown to be effective and safe in a neonatal calf model will most likely constitute the next advance for clinical trials in humans. However, developing an effective and inexpensive vaccination, as well as complementing structural preventive measures, would most decisively reduce the global cryptosporidiosis burden.